(untitled) (Colombia Medica, 1990)
In Cali, Colombia, from September 1st, 1988, to August 31, 1989, prospective data on neonatal mortality were collected from hospitals and other institutions of the National Health System of Colombia. Evitable causes of mortality were investigated using the available human and technological resources. There were 19,322 births and 355 neonatal deaths. In the highest attention level (III), the mortality rate was 24.1%, while in lower levels (I and II), it was 10.7%. The neonatal mortality rate for the whole system was 18.4% live births. Still, when a weight of 1000g or less at birth and the presence of congenital anomalies incompatible with life were considered, the mortality rate diminished to 13.5%. Among low birth weight babies (< 2500g), 77.8% of deaths were found. Perinatal asphyxia with meconium aspiration syndrome and infectious diseases were the two more common causes of death. Data obtained were compared to those reported in the literature. As far as it is known, this is the first report of neonatal mortality in a Latin American city where regionalization of medical attention has been achieved.